Studi Kepuasan Pengguna Jasa Angkutan Petikemas Terhadap Pelayanan Kereta Api dan Kapal Logistik (Studi Kasus: Koridor Surabaya-Jakarta) - Rahayu Pradita; Hera Widyastuti (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2020)
The freight train becomes an alternative mode of freight transport, especially containers. The container train can transport large loads in one way so it is more efficient. The trip can be reached by train faster due to the unconstrained congestion. The total number of carrier train users from Surabaya to be the most famous performance of the container train itself. This research aims to determine the performance and satisfaction of the service users, knowing the characteristics of the service users delivery goods, the mode selection factor between the ship and the container train, and recommend improvement of service advice on shipping goods with containers. Data collection In this study used a survey method with a questionnaire based on revealed preference with analysis with binary logistic regression, Customer Satisfaction Index (CSI). The results of the analysis showed that the factors influencing the delivery mode of goods between containers and marine vessels are the origin of goods and the purpose of goods. The results of customer satisfaction analysis of Kalimas Station and container Terminal of Surabaya are 0.794 and 0.8.